Ownership, Compensation and Board Diversity as Innovation Drivers: A Comparison of U.S. and Canadian Firms - Atallah, Gamal; De Fuentes, Claudia; Panasian, Christine A. (Université d'Ottawa | University of Ottawa, 2020)
Using a large sample of North American firms, from 1999 to 2016, we investigate the effect of corporate governance structures, specifically ownership, board characteristics, and executive compensation contracts on innovation intensity and output. We consider both R&D expenditures and patents as innovation proxies and evaluate consequences of the economic downturns of 2000 and 2008. We find that R&D investment increases with ownership by institutional blockholders and with the number of institutional owners, confirming the key role institutions play in innovation activities of firms. We observe higher R&D levels for firms with more independent boards, more females board members and more outside directorships held by directors. We report that firms with CEO/chair of the board duality have lower R&D intensity, as do firms with higher ownership by directors and with a higher mean board age. Innovation is negatively related to CEO salary levels, but positively related to the ratio of incentives to total compensation, confirming that incentives contribute to aligning shareholders and management interests, which leads to better long-term decisions. However, those incentives reduce the number of patents. We do not find any systematic changes in R&D for the 2000 recession, however there is an increase for the 2008 financial crisis.
Keywords: Gouvernance d'entreprise; Finance corporative; Innovation; R&D; Canada; Étais-Unis